SELF-EMULSIFYING DRUG DELIVERY SYSTEMS (SEDDS): EXCIPIENT SELECTION, FORMULATION AND CHARACTERIZATION - Ivaylo Pehlivanov (Peytchinski Publishing, 2020)
There is a great number of active pharmaceutical ingredients (APIs) in development that have low solubility and/or low permeability. The oral administration is usually connected with low bioavailability, high Intra- and inter- variability of the plasma levels and lack of dose proportionality. Formulating such APIs in SEDDS ameliorates the solubility, permeability and bioavailability profiles with reproducible plasma concentrations. SEDDS are mixtures of different oils and emulgators, ideally isotropic mixtures. Often they contain co-emulsifiers and co-solvents. After dispersion in the gastric fluids, they self-emulsify to fine O/W or W/O/W emulsions having dimensions of the dispersed phase in the range 100-300 nm and in some cases under 100nm. Surfactants' concentration, surfactant to oil ratio, emulsion polarity, droplet dimension and surface charge are important parameters that influence API absorption from SEDDS when orally administered. These Drug Delivery Systems can facilitate permeation process, but preferable absorption path is through the lymphatic system that leads to bypassing the hepatic first-pass metabolism. The use of in-vitro dispersion and digestion methods permit to a better understanding of the role of the processes that the lipids undergo in the gastrointestinal tract (GIT) during the solubilization of these systems. The aim of the article is to present a short overview of SEDDS as a strategy to bioavailability improvement, basic principles of excipient selection during their formulation and their characterisation.